An active Mitochondrial Complex II Present in Mature Seeds Contains an Embryo-Specific Iron–Sulfur Subunit Regulated by ABA and bZIP53 and Is Involved in Germination and Seedling Establishment - Restovic, Franko; Espinoza-Corral, Roberto; Gómez, Isabel; Vicente-Carbajosa, Jesús; Jordana, Xavier (Frontiers in Plant Science, 2017)
Complex II (succinate dehydrogenase) is an essential mitochondrial enzyme involved in both the tricarboxylic acid cycle and the respiratory chain. In Arabidopsis thaliana, its iron-sulfur subunit (SDH2) is encoded by three genes, one of them (SDH2.3) being specifically expressed during seed maturation in the embryo. Here we show that seed SDH2.3 expression is regulated by abscisic acid (ABA) and we define the promoter region (-114 to +49) possessing all the cis-elements necessary and sufficient for high expression in seeds. This region includes between -114 and -32 three ABRE (abscisic acid-responsive) elements and one RY-enhancer like element, and we demonstrate that these elements, although necessary, are not sufficient for seed expression, our results supporting a role for the region encoding the 5’ untranslated region (+1 to +49). The SDH2.3 promoter is activated in leaf protoplasts by heterodimers between the basic leucine zipper transcription factors bZIP53 (group S1) and bZIP10 (group C) acting through the ABRE elements, and by the B3 domain transcription factor abscisic acid insensitive 3 (ABI3). The in vivo role of bZIP53 is further supported by decreased SDH2.3 expression in a knockdown bzip53 mutant. By using the protein synthesis inhibitor cycloheximide and sdh2 mutants we have been able to conclusively show that complex II is already present in mature embryos before imbibition, and contains mainly SDH2.3 as iron-sulfur subunit. This complex plays a role during seed germination sensu-stricto since we have previously shown that seeds lacking SDH2.3 show retarded germination and now we demonstrate that low concentrations of thenoyltrifluoroacetone (TTFA), a complex II inhibitor, also delay germination. Furthermore, complex II inhibitors completely block hypocotyl elongation in the dark and seedling establishment in the light, highlighting an essential role of complex II in the acquisition of photosynthetic competence and the transition from heterotrophy to autotrophy.